Peran Pembayaran Digital Payment Gateway Dalam Meningkatkan Kinerja Keuangan Pada UMKM - Angelia Alfatwa Rusandi Siregar; Heny Triastuti Kurnia Ningsih; Pretty Nur A’yuni Laoli (Universitas 17 Agustus 1945 Semarang, 2023)
The emergence of the term Financial Technology (fintech) today is one of the changes caused by current developments. Financial technology (fintech) has several types, one of which is payment gateway. Currently, MSMEs in Indonesia have an important role in Indonesia, namely improving its economy and being able to accelerate regional development. The aim of this research is how influential the use of digital payment